The Effect of Group Guidance Services Through Homeroom Techniques in Improving Self Esteem for Students in Madrasah - Hafsah Dahni Rahmayani Siregar; Ali Daud Hasibuan (Edumaspul: Jurnal Pendidikan, 2024)
Self-esteem is a person's attitude towards their views and beliefs about themselves, including accepting all their weaknesses and strengths and always appreciating and seeing themselves positively without feeling disappointed with what they do. This positive behavior towards oneself can create a feeling that one has value and benefits. This research aims to determine the effectiveness of group guidance services using the homeroom technique in increasing students' self-esteem in madrasas. The research method used is quantitative, with a pre-experimental design and a one-group pretest-posttest design. The population of this study consisted of two classes of class VIII students at MTs S Zakiyun Najah, with a total of 31 students. A sample of 8 students with low self-esteem levels was taken from this population using a purposive sampling technique. Data was collected using a non-test instrument in the form of a questionnaire. Data analysis was carried out using the Wilcoxon Signed Ranks Test. The results of this study indicate the significance of the value of asymp. Sig (2-tailed) is smaller than 0.05, namely 0.011. Therefore, it can be concluded that group guidance services using the homeroom technique effectively increase students' self-esteem.